Better breast cancer detection. - Moore, S.K (IEEE spectrum)
X-rays go digital, computers read film, and chemicals mark tumors, but will these new technologies make it in the clinic? The imaging technologies considered for breast cancer include film-screen mammography, full field digital mammography, ultrasound, magnetic resonance imaging, scintimammography, thermography, electrical impedance imaging, optical imaging, electric potential measurement, positron emission tomography, novel ultrasound techniques, elastography, magnetic resonance spectroscopy, thermoacoustic computed tomography, microwave imaging, Hall-effect imaging and magneto-mammography